Coordenadas geométricas em funções paramétricas no winplot - Silva, Francisco Allan Quintela (2014)
From the beginning, the numeric sequences and series generated interest among mathematicians. Your present applicability is extensive and includes the refined calculation of the surface area and volume of a variety of solids. In this work we will use the differences between the elements of a finite sequence in order to find laws that express the trends contained therein. We will also see how a simple study about arithmetic progressions of various orders is able to provide curves's parametric functions through predefined points, of surfaces containing predefined curves or even regions of the R³ localized between two given surfaces. Moreover, we will can, with the aid of the computational program Winplot, visualize the curves, surfaces, or regions obtained in each example of our study, in addition to eventually check points of relative maximum and minimum of a curve or calculate the area of a surface and the volume of a limited region of R³, all of this with a necessary and previous theoretical background.